2018
DOI: 10.1002/2017jd028243
|View full text |Cite
|
Sign up to set email alerts
|

How Accurately Can the Air Temperature Lapse Rate Over the Tibetan Plateau Be Estimated From MODIS LSTs?

Abstract: The air temperature lapse rate (TLR) is a key parameter for interpolating air temperature data in high mountainous regions such as the Tibetan Plateau (TP). The Moderate Resolution Imaging Spectroradiometer (MODIS) land surface temperature (LST) has been frequently used for estimating air temperature during the past decade, but its performance in estimating the TLR in the TP has seldom been investigated. This study employed two methods in estimating the TLR based on MODIS LSTs compared with the “observed” TLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 80 publications
1
18
0
Order By: Relevance
“…A comparison of lapse rates in Finnish Lapland for LST versus T air showed very little correspondence between the two, because of the elevational gradient in surface types (Pepin et al, 2018). In the Tibetan Plateau in contrast, lapse rates estimated for daily mean temperature from LST were found to show similar seasonal patterns to those based on T air (Zhang, Zhang, Zhang, Che, et al, 2018). There have been relatively few detailed studies of the difference between T air and LST at extreme high elevations above 5,000 m, but those that have been performed tend to show increased variance in the difference, a lower correlation between T air and LST, and larger mean differences (Pepin et al, 2016).…”
Section: Past Studiesmentioning
confidence: 85%
“…A comparison of lapse rates in Finnish Lapland for LST versus T air showed very little correspondence between the two, because of the elevational gradient in surface types (Pepin et al, 2018). In the Tibetan Plateau in contrast, lapse rates estimated for daily mean temperature from LST were found to show similar seasonal patterns to those based on T air (Zhang, Zhang, Zhang, Che, et al, 2018). There have been relatively few detailed studies of the difference between T air and LST at extreme high elevations above 5,000 m, but those that have been performed tend to show increased variance in the difference, a lower correlation between T air and LST, and larger mean differences (Pepin et al, 2016).…”
Section: Past Studiesmentioning
confidence: 85%
“…Some studies have found that there is a strong relationship between the mean LST and mean near-surface air temperature [13][14][15][16], and the seasonal pattern of monthly mean land-surface TLR is very similar to that of the near-surface air TLR [17]. However, as the LST is influenced by the surface regime [18,19], the relationship between them is not always stable.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between DEM and LST is inverse due to the effect of NSTLR. The LST decreased with the increase of elevation (He et al 2018;Jain et al 2008;Lakshmi et al 2001;Zhang et al 2018). The results for different dates are shown in Table 1 The NSTLR values of the study area varies with time (Table 4).…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, in mountainous and many natural environments, the LST-DEM feature space will be influenced by other parameters. For example, a decrease of LST was reported with the increase in elevation (Jain et al 2008;Verhoest et al 2012;Zhang et al 2018). Similarly, environmental parameters including topographic conditions, solar local incident angle, and surface biophysical properties influence LST based on the LST-DEM feature space.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation